Medições infinitesimais de variação de energia em sistemas quânticos - Gabriel Pimenta Martins (2017)
Thermodynamical properties of quantum systems have been the object of study from many recent papers. In this dissertation, we begin with a brief review of quantum thermodynamics papers, where we focus on the rst law. We show that there are many different denitions of work and heat on quantum systems. We focus on one of the most usual denitions andwe present a recent work from Augusto Roncaglia et al. [1]. On this paper, they propose a method to measure the variation of the internal energy of a quantum system between two instants of time with a single measure by making the system interact with an ancilla twice. This method will be used as a starting point for this dissertation. We will explain how totransform the measurement protocol into one that continuously monitors a system and we will describe some conditions that the system must obey to make this monitoring possible. We show how the ancilla, which will also serve as the measurement apparatus, work and we will dene a quality factor for the measures. At last, we will study a specic system and will show how to use the protocol to obtain the time-dependance of an unknown hamiltonian. In order to do this, we use an algorithm that simulates the measurements proposed here and show that the protocol can not only effectively reconstruct the unknown hamiltonian but also obtain the total work and heat exchanged between the system and a reservoir.